Building history awareness through Kartini Film (2017) in History Subject learning at the high school - Merryasni, Arlyan (Ittishal Educational Research Journal, 2023)
A problem that often occurs during the process of learning history at the high school level is the tendency to receive information that is only delivered from teachers to students. The main goal in history learning is to build students' historical awareness individually or in groups achieved through a learning process. History subject learning in schools is more likely to use the lecture method so that history is often analogous to memorizing an event or figures in history. This kind of method pays less attention to intellectual skills and understanding of history awareness for the students. Therefore, a learning strategy is needed to build historical awareness for students so that history is no longer seen as mere rote knowledge. Currently, Generation Z is still in high school. Their general nature tends to be practical, which makes them ignorant of history. Historical films, especially Kartini film (2017), can invite students to understand the importance of historical awareness about past events that affect the present. In this study, the authors used a qualitative approach where this research is descriptive. This study aims to find out or describe the reality of the events under investigation to find out and understand how to build historical awareness through the Kartini film for generation Z. Results of this study show that students can realize historical events through the Kartini film and even able to explain in detail about the problems that occurred at that time and bring it to today's modern issues. Students can build historical values through film because film involves all the emotions within themselves. Learning history is no longer just sharing information from teachers to students but can be through the feelings presented in historical films.